CEGAH BULLYING, JAGA KESEHATAN MENTAL: PSIKOEDUKASI SISWA DENGAN METODE PROBLEM BASED LEARNING - Nugroho, Adyatma Susilo; Fanda, Keisya Shaskia Dea; Wangko, Samuel Miracle; Andika, Andre Novan; Sudibyo, Rafi Qurniawan Bayu; Wibowo, Doddy Hendro; Setiarsih, Hanik (Universitas Kristen Satya Wacana Salatiga, 2024)
Bullying often occurs in teenagers and mostly occurs in junior high school students. Therefore, school institutions try to carry out various efforts to prevent bullying. Community service aims to prevent bullying based on psychoeducation activities with an understanding of the problem of bullying at school and how to prevent bullying at school. The activity was carried out at SMP Negeri II Boyolali, for participants namely class VIII-B, totaling 26 students. Classical guidance is carried out using psychoeducation based on the Problem-Based Learning (PBL) method. Students show enthusiasm and activeness in participating in activities. The results of the learning process evaluation show that they have a better understanding of bullying after following psychoeducation. This activity is expected to be beneficial for students to improve their mental and emotional well-being, create a safe and comfortable learning environment, and build positive social interactions.